A model for alleviating work pressures and enhancing teachers' resilience - Al-Jarf, Reima (Journal of Psychology and Behavior Studies, 2024)
Teaching is a complex task that requires knowledge of what to teach, how to teach it, and how to cope with educational challenges. To perform their duties effectively, teachers’ mental well-being and inner states are essential. This study aims to define teacher resilience, give examples of the stressors and challenges that EFL/ESL college instructors face and the factors that lead to attrition and burnout. It also aims to propose strategies for coping with negative stressors. Results of a survey with a sample of EFL/ESL college instructors at five higher education institutions in Saudi Arabia who teach language, linguistics, translation and interpreting courses to undergraduate students showed that they face intellectual, emotional, and service-related stressors and challenges that impact their well-being and effectiveness such as high workload, limited support, meeting deadlines, managing their time effectively, students’ behavior and attitudes, classroom management and health concerns, financial and economic issues, balancing their work and personal, and lack of support and recognition. In addition, some instructors complained of lack of motivation and enthusiasm, fatigue, headaches, irritability, anxiety, depression, and difficulty concentrating. To combat stress, mental and emotional challenges that some instructors face, this study proposes some coping strategies based on the principles of positive psychology to help foster teacher resilience, maintain a strong and effective teaching workforce, and empower educators to thrive in their profession. These coping strategies cover psychological, pedagogical, interpersonal, and pragmatic aspects such as identifying the signs of stress, prioritizing self-care and well-being, setting achievable goals, time management and organization, embracing flexibility and adaptability, adopting a positive mindset, classroom management techniques, advocating for resources and support, attending professional development workshops, building/joining a strong support network, collaborating with other colleagues to share ideas and strategies, reflecting on and assessing their teaching practices, practicing mindfulness, quick relaxation techniques, visualization, progressive muscle relaxation, deep breathing, listening to music, regulating emotional responses, and celebrating small wins. The coping strategies posed herein are described in detail.